Examining the Water Literacy Levels of High School Students According to Some Variables - SÖZCÜ, Ufuk; TÜRKER, Abdullah (Asian Journal of Education and Training, 2020)
As the world population increases, the issue of using freshwater resources efficiently becomes more important. Using water, which is an indispensable resource for life, consciously and sustainably, to be sensitive, in short, to be water literate is a necessity for all citizens of the world. Turkey is a country living water scarcity. Therefore, it is a country where water literacy studies should conduct. As it is the first comprehensive study of water literacy in Turkey, the present study becomes significant in the field. This study aims to determine the water literacy levels of high school students in Turkey. In the present study, Data was gathered through the Water Literacy Questionnaire. The Water Literacy Questionnaire was designed by Sözcü and Türker (2020) and consists of three sections. The questionnaire was applied to 3202 high school students living in different regions. As a result of the study, the water literacy of high school students was at 'Good Level' in general. When the sub-dimensions of water literacy were analyzed, high school students were very good at water-saving and good at water sensitivity, but remain at medium level in terms of water consciousness. In light of the results, some recommendations have been made to increase water literacy.